Utilizing Geographic Information Systems to Map Earthquake Disaster Risk in the Citatah Karst Industrial Area - Haikal Muhammad Ihsan; Alwan Ramdani; Inayatul Fuadah; Acep Supriadi; Shafira Himayah (Universitas Lambung Mangkurat, 2025)
The Lembang fault is located very close to the Citatah industrial area in West Bandung Regency. This location makes the Citatah industrial area highly susceptible to earthquakes caused by the Lembang Fault.. The aim of this research is to map the distribution of factories which are part of the earthquake risk, danger and vulnerability zone. The method used is a survey method using the Geographic Information System application. Information on vulnerabilities, hazards and risks is obtained through INARISK, while factory distribution is obtained by direct site surveys. Based on the analysis, it was found that the Citatah karst area has 34 mining factories spread close to the main road. The vulnerability assessment describes that 33 factories are in locations with high vulnerability, while moderate vulnerability consists of 1 factory. The hazard analysis describes that there are 20 factories in the high-risk zone, 10 factories in the medium risk zone and 4 factories in the low-risk zone. The risk of earthquake disasters has three classifications, namely low, medium and high. Based on the analysis, it was found that 26 factories were in the high-risk zone and 8 factories were in the medium zone. This area is close to the Lembang fault, so it is at high and medium risk. The low-risk zone is located at low elevation and the furthest part of the karst area from the Lembang fault. This research can be useful in for spatial planning and mitigation strategies in earthquake-prone areas.